(untitled) (مجلة ديالى للبحوث الانسانية, 2022)
Investigating Arabic Satire with Special Reference to Translating Satirical Expressions in the Glorious Quran The present study aims at exploring the interesting genre of satire in general with special emphasis on Arabic satire which is the core subject of this research. This aim would be achieved through studying the unique language of satire and its special vocabulary, types and distinctive characteristics. The second part of the study discusses the translation of the Glorious Quran into English by analyzing excerpts from three different translations so as to be able to present an assessment of the quality of the TL version, and find out how successful, faithful and competent were the translations in reproducing expressions of satire in English. In doing so the study came to the conclusion that the main difficulty lies in grasping the SL intended meaning (both denotative and connotative). Moreover, it was found the literal translation was the favorable approach in rendering Quranic satirical expressions usually accompanied with paraphrasing, extension and commentary.